Comparative analysis of bone consolidation chronology in claw toes operated through minimal invasive osteotomies in diabetic vs. non-diabetic patients - Batalla-Salgado, Cristina; Ferrer-Torregrosa, Javier; Muñoz-Piqueras, Francisco; Muñoz Bautista, Miguel; Barrios, Carlos (Frontiers in Surgery, 2022)
Objective To compare bone healing time in osteotomies performed in claw toes correction through minimal invasive surgery in diabetic vs. non-diabetic patients. The relation between the patient's ages and the American Orthopedic Foot and Ankle Surgery Society (AOFAS) functional scores before and after surgery was also analyze in the two types of patients. Method A series of 45 women, 23 of them suffering from Diabetes Mellitus, were operated to correct claw toes. The surgery was always performed through minimal invasive digital osteotomies. After the intervention, bone healing was controlled by a fluoroscopic weekly follow-up until a complete bone consolidation was reached. Bone healing time was compared in in two groups of patients, diabetic and non-diabetic. All patients were evaluated with AOFAS scale 48 h before and 90 days after the intervention. Results The time of bone healing ranged from 24 to 40 days after the surgery and took shorter time of consolidation in non-diabetic patients although the Mann Withney U test did not show statistically significant differences (p = 0,409, effect size (ES) = 0,14 [-0.20 to 0.45]) between both groups. A statistically significant association (r = 0.71, R2 = 50%, p < 0.001) was found between the healing days and the day of medical discharge, also between the ages of the patients and the medial discharge (r = 0.36, R2 = 13%, p < 0.001). However, no statistically significant associations were found between pre-intervention glycemia and days of bone consolidation, neither in medical discharge (r = 0.07, p = 0.646 y r = 0.07, p = 0.648, respectively). AOFAS test scores and the diabetes status showed statistically significant differences, both in the main effect of Diabetes (F[1,41] = 9.41, p = 0.004) as in the interaction between diabetes and age (F[1,41] = 9.17, p = 0.004). Conclusions The bone healing time in claw toes operated through minimal invasive osteotomy surgery is not influenced by the presence of diabetes. The consolidation speed and the improvement in AOFAS functional scale score post-surgery in diabetic and elder patients was related to duration of the medical discharge.